Representation of Cultural Values and Meanings in the Tunjuk Ajar Tegur Sapo Tradition for Newlyweds in the Muaro Jambi Malay Community: An Ethnolinguistics Study - Muhammad Muslim Nasution; Julisah Izar; Alwin Teniro; Amru Bin As (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The previous studies on Malay wedding traditions have largely focused on describing lexical meanings or general cultural elements, while the representation of cultural values ??embedded in the integrity of ritual icons and proverbs has not been comprehensively examined. This study aimed to describe the representation of cultural meanings and values ??in the Tunjuk Ajar Tegur Sapo tradition during traditional Malay wedding ceremonies in Muaro Jambi regency, Jambi Province. Using a qualitative descriptive method through an ethnolinguistic approach, this study examined the relationship between language, culture, and value systems. Data are sourced from recordings of traditional speech, verbal symbols, and customary advice with informants, traditional leaders and practitioners directly involved. Data collection was carried out through a free-engagement conversation technique to record authentic interactions. The results reveal that the Tunjuk Ajar Tegur Sapo tradition is a concrete manifestation of the values ??of responsibility, harmony, and social ethics symbolically represented through expressions of affection and collective social support. The novelty of this study lies in the integration of analysis between physical icons and proverbs as an integrated system that legitimizes community moral standards. Theoretically, this research contributes to strengthening ethnolinguistic studies by proving that ritual speech is not just a means of communication, but a vital instrument in maintaining the stability of cultural values ??and mediating the transition of social life in the Muaro Jambi Malay community.